Monitoring the agri-food system in Myanmar: Agricultural commodity traders - May 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand how Myanmar’s crop marketing system has been affected by political instability, phone interviews were conducted in May with 78 agricultural commodity traders. Key Findings: ▪ Although there have been modest improvements since the previous survey in March 2021, disruptions to transportation, payments, credit, and telecommunications are still widespread, with 94 percent of interviewed traders in May experiencing at least one business disruption. ▪ Credit for trading operations is a much more frequently cited difficulty compared to a year ago. Forty percent of traders reported challenges obtaining new credit or loans in May 2021 and 37 percent reported difficulties repaying loans, compared to just 15 percent and 10 percent in May 2020, respectively. ▪ Although credit demand increased, there has been a decline in credit provision to farmers. The share of traders offering credit dropped by 18 percentage points in May 2021 compared to May 2020, and the average value of credit lent by traders still lending is 30 percent lower. Unwillingness to lend may be related to increased difficulties in loan recovery–48 percent of traders experienced difficulties collecting repayment on credit lent to farmers in May 2021 compared to 27 percent in May 2020. ▪ There has been a dramatic reduction in adherence to COVID-19 preventive measures compared to the same period a year ago, despite the third wave of the pandemic underway and the presence of new and more contagious variants. ▪ Cash payments have become increasingly dominant for purchases and sales as bank transfers and mobile payments are rarely being used. The use of the Hundi system has also decreased in recent months. ▪ Crop volumes traded are down 12 percent compared to a year ago and sesame prices have dropped by one-third their value.